"The Bagnios of Algiers" and "The Great Sultana" : Two Plays of Captivity. - Cervantes, Miguel de (University of Pennsylvania Press, 2012)
The Bagnios of Algiers and The Great Sultana enact the intense imaginative engagement of early modern Spain with the Muslim worlds of the Mediterranean. They also reflect Cervantes's first-hand experience of captivity in North Africa, which had a crucial impact on his writing. The religious and political rivalries on this "forgotten frontier," as Andrew Hess terms it (1978), serve as the backdrop to the complex set of relationships and identities explored in the texts.